Estudo da termoestabilidade de proteínas cold shock homólogas por modelos teóricos simplificados. - BORGES, Ueliton Galdino (2018)
The functions that proteins perform are extremely important to living things, this function is directly linked to its thermostability, and may undergo temperature variations. As thermostability is the focus of this work, specifically addressing the different transition temperatures between the unfolding / unfolding of the homologous proteins, using as study object and starting point for these and other questions, Cold Shock homologous proteins of the psychophilic bacteria, Listeria monocytogenes (Cs-pLa), mesophilic, Bacillus caldolyticus (Bs-CspB), thermophilic, Bacillus subtilis (Bc-Csp) and hyperthermophilic, Thermotoga maritime (Tm-Csp), considering the variations in temperature and their interactions, taking into account the aspects of these proteins as well as their identity and similarity. It may be noted that there are several methods of determining protein structures in both in vitro and in silicon. In this work, we propose an in silico method, which discusses the simulation of protein structure and optimization, considering simultaneously the energetic and structural aspects of proteins. For the Molecular Dynamics simulations the GROMACS software was used. To better understand these thermodynamic differences and the thermostability that occurs due to the variations of the chains in Cold Shock proteins proteins. We performed computational simulations taking into account only the alpha carbon (CĮ) that considerably reduces the simulation time. The theoretical results found corroborated with experimental data showing that the Cold Shock protein Hyperthermophilic Thermotoga marine bacteria present the highest value of folding temperature and the largest difference of RMSD among all four Cold Shock proteins currently studied. Due to the finding that the Cold Shock proteins presented favorable thermostability to the residue changes that can be carried out in order to be used in processes that require a change in temperature.